Cancer in Māori: lessons from prostate, colorectal and gastric cancer and progress in hereditary stomach cancer in New Zealand. (20th December 2012) - Blair, Vanessa; Kahokehr, Arman; Sammour, Tarik
Abstract: Persisting ethnic disparities in cancer incidence and outcomes exist between Māori and non‐Māori in Aotearoa/New Zealand. It is difficult to disentangle the complex interplay of environmental and genetic factors that contribute to the variation in cancer statistics between these two groups. In Māori, the sites of highest cancer incidence are the prostate in men, breast in women and lung in both – the next most common cancers in Māori are colorectal and stomach cancer. This paper discusses colorectal, prostate and stomach cancer in Māori to illustrate selected issues that impact on cancer care. Colorectal cancer is discussed to illustrate the importance of accurate cancer statistics to focus management strategies. Prostate cancer in Māori is reviewed – an area where cultural factors impact on care delivery. Sporadic stomach cancer in New Zealand is used to show how sub‐classification of different types of cancer can be important and illustrate the breadth of putative causal factors. Then follows an overview of developments in hereditary gastric cancer in New Zealand in the last 15 years, showing how successful clinical and research partnerships can improve patient outcomes. One example is the Kimi Hauora Clinic, which provides support to cancer patients, mutation carriers and their families, helping them navigate the interface with the many health‐care professionals involved in the multidisciplinary care of cancer patients in the 21st century.